ANALISIS PERBANDINGAN PENGUNGKAPAN LAPORAN KEUANGAN KONSOLIDASI BERDASARKAN PSAK 110 - Prita Karina Diandra; Kurnia Mulindawati Hasriyono; Irene Kurnianingtyas; Verene Barbie (JURNAL LENTERA AKUNTANSI, 2024)
A consolidated financial statement is a report that presents financial information reflecting the financial position and operational performance of a parent company along with one or more subsidiaries as a single economic entity (Khaerudin, dkk., 2023). The preparation of consolidated financial statements is based on the end-period reports of each subsidiary, which are then combined by the parent company to produce the consolidated financial statements (Saputro, dkk., 2023). Using a quantitative method, this study was conducted by the author to compare consolidated financial statements between the banking sector and the food and beverage sector in accordance with the provisions of Financial Accounting Standards (PSAK) 110. The analysis results indicate that PT Bank Central Asia Tbk outperforms PT Indofood Sukses Makmur Tbk due to differences in the business sectors they operate in. Compliance with applicable Financial Accounting Standards plays a crucial role in establishing a company's reputation as a transparent and highly ethical entity in its financial reporting. This approach also enhances the company's image in the eyes of investors and supports long-term business sustainability.